Shift of infrared vibrational spectra and H2O activation on PtCu alloy clusters - Yanbiao Wang (AIP Advances, 2020)
Despite significant progress made in the past decades, there is still lack of insights into the reactivity of H2O on metal catalysts, in particular, the effect of vibrational modes of H2O in reaction. Here, we report, to the best of our knowledge, the first ab initio study on the correlation between the activation of H2O and the shift of infrared vibrational spectra on the Cu(10-n)Ptn (n = 0–10) alloy clusters. The results revealed that the alloying effect plays an important role in promoting H2O dissociation on Cu(10-n)Ptn (n = 7–9) clusters. The interaction between H2O and substrates fundamentally originates from the band of d-states. The red-shift of the center of v1 and v3 modes of H2O adsorbed relative to that of isolated H2O is a good descriptor of H2O activation. The results probably provide a good opportunity to characterize the reactivity of small molecules on catalysts by infrared vibrational spectra.